Impact of a constructivist approach on students' mathematical communication ability: A quasi-experimental study - Putri, Syilvi Jania; Jamaan, Elita Zusti (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: Mathematics is a compulsory subject in education due to its extensive application in daily life. However, in reality, many students still face difficulties in understanding and learning mathematics. One of the key competencies in mathematics education that students need to master is mathematical communication skills. This study aims to analyze the effect of applying the constructivism approach on the mathematical communication skills of grade VIII students at SMP Negeri 1 Bayang Utara. Method: This study uses a quasi-experimental method with a randomized control group only design. The population in this study is all grade VIII students, and the sampling technique is carried out by saturated samples. The sample consisted of two classes, namely an experimental class that used a constructivist approach and a control class that used conventional learning methods. The research instrument is in the form of an essay test that measures students' mathematical communication skills. Findings: The results showed that the average mathematical communication ability of students in the experimental class (81.67) was higher than that of the control class (71.64). Statistical tests with t-tests showed that there was a significant difference between the two groups at a real level of α = 0.05. This proves that the constructivism approach has a significant positive influence on students' mathematical communication skills. Significance: The results of this study show that the constructivist approach enhances students' mathematical communication skills by encouraging active knowledge construction through interaction and exploration. This helps students convey mathematical ideas more effectively, improving their ability to explain problems clearly and logically. These findings imply that the constructivist approach can support the improvement of mathematical learning outcomes, particularly in communication skills, which are essential for developing critical thinking and problem-solving abilities.